Qualitative Analysis of Structural Holes in Emerging Media Industries：Evidence from Taiwan's OTT Industry - Wen-Yi Hsu (International Telecommunications Society (ITS), 2024)
Structural hole theory can be used to explain the advantages of an individual or firms in the economic structure. From a network perspective, this study analyzes the relationship between local OTT operators in Taiwan, the relationship with large international OTTs, and the bridges or structural hole spanners. The researcher conducted semi-structured interviews with major players in Taiwan's OTT industry, and employs the grounded theory approach, systematically inducting and analyzing data. Based on the perspectives of local OTT operators describing the main competitors in the Taiwanese OTT market, the research identifies major international OTT, particularly Netflix, as the hub and structural hole spanner. This study maps 'Taiwan's OTT industry structural holes', and further explore whether Taiwan's local OTT operators are able to act as bridges or structural hole spanners. This research found that relationships among local Taiwanese players are loose, with most situated at the periphery of the industry network; Netflix serves as a network bridge. Netflix occupies the central position in Taiwan's OTT industry network as a structural hole spanner. Netflix benefits from being a structural hole spanner., while local Taiwanese players do not form mutually beneficial partnerships. The connection between local Taiwanese OTT players and international operator increasingly exhibits reinforced structural holes. The existence of structural holes in Taiwan's OTT industry and the possibility for local operators to gain advantages. This study also proposes types and analysis of structural holes in Taiwan's OTT industry and analysis of structural holes for local OTT operators in Taiwan. This underscores the limited key resources of local operators. Overall, there is no significant advantage for domestic operators. To remain competitive, local OTT operators must seek new opportunities within these structural holes
Keywords: 330; OTT; center-periphery theory; structural hole theory; qualitative structural analysis